Epigenetic stability of exhausted T cells limits durability of reinvigoration by PD-1 blockade - Pauken, Kristen E. (Science, 2016)
Blocking Programmed Death–1 (PD-1) can reinvigorate exhausted CD8 Tcells (T(EX)) and improve control of chronic infections and cancer. However, whether blocking PD-1 can reprogram T(EX) into durable memory Tcells (T(MEM)) is unclear. We found that reinvigoration of T(EX) in mice by PD-L1 blockade caused minimal memory development. After blockade, reinvigorated T(EX) became reexhausted if antigen concentration remained high and failed to become T(MEM) upon antigen clearance. T(EX) acquired an epigenetic profile distinct from that of effector Tcells (T(EFF)) and T(MEM) cells that was minimally remodeled after PD-L1 blockade. This finding suggests that T(EX) are a distinct lineage of CD8 Tcells. Nevertheless, PD-1 pathway blockade resulted in transcriptional rewiring and reengagement of effector circuitry in the T(EX) epigenetic landscape. These data indicate that epigenetic fate inflexibility may limit current immunotherapies.